Analisis Dan Pemeteaan Daerah Banjir Menggunakan HEC-RAS Dan SIG Di Kota Bengkulu (Studi Kasus Air Bengkulu Hilir) - Melki Sanjaya; Meilani Belladona (MAJALAH TEKNIK SIMES, 2020)
Abstract Flooding in Bengkulu city is an event that occurs every year. One area that is often affected by floods is the downstream area of ??the Air Bengkulu River Basin. Flooding in the Air Bengkulu Hilir watershed is caused by an increase in water discharge due to high rainfall. This study aims to create a flood inundation map. This map was created by modeling. flood inundation in the Air Bengkulu Hilir watershed area through a simulation of flood flow. Flood inundation modeling is carried out by utilizing a special mode of analysis in Geographic Information Systems (GIS) for the creation of river geometry as well as a HEC-RAS hydraulic flow simulation program. The method of making maps with several stages, namely the first rainfall analysis, calculation of drainage coefficient and land cover. Secondly, the preparation of digital elevation data (DEM) as a source of data forming river geometry, then the flow simulation uses the flood data of the flood plan in 5 and 10 years at 1789,687 m3 / second and 1830.15 m3 / second. Flood generation is displayed automatically through the RAS Mapper site in ArcGIS. Depth The results of the flood inundation map based on the flood discharge plan for 5 and 10 years are 0 - 10,534 m and 0 - 10,571 m identified areas are Surabaya, Semarang, Bentiring, Tanjung Jaya, Tanjung Agung, Suka Merindu, Rawa Makmur, and Kampung Kelawi.